PbS/CdS/ZnO nanowire arrays: Synthesis, structural, optical, electrical, and photoelectrochemical properties - Holi A.M.; Al-Zahrani A.A.; Najm A.S.; Chelvanathan P.; Amin N. (Elsevier B.V., 2023)
Cadmium sulfide; Electrochemistry; II-VI semiconductors; IV-VI semiconductors; Nanowires; Optical properties; Oxide minerals; Zinc oxide; Hydrothermal methods; Nanowire arrays; Photoelectrochemical performance; Photoelectrochemical properties; Photoresponses; Successive ionic layer adsorption and reactions; VIS spectroscopy; ZnO nanowire arrays; Lead compounds